Relation of Salivary Alpha-Amylase (sAA) Concentration to Fatigue Biomarkers in Palm Oil Office Workers in Jambi Province: Preliminary Study - Kusmawan, David; Eka Rini, Willia Novita; Aurora, Wahyu Indah Dewi (UI Scholars Hub, 2023)
The salivary α-amylase (sAA) concentration has a potential role as a biological indicator of occupational fatigue. This study aimed to determine the levels of sAA and its influencing factors. This research used a cross-sectional design with a sample of 40 office staff respondents at PT. X (Persero). Mental workload (MWL), sleep quality, and occupational fatigue were measured using the NASA-Total Load Index (TLX), Pittsburgh Sleep Quality Index, and Industrial Fatigue Research Committee, respectively. Meanwhile, the basic sAA levels was measured through the sandwich enzyme-linked immunosorbent assay method using the Bioenzy® Kit Assay. Descriptive analysis showed that the workers were mostly men, 75% of which had a high education level and 72.5% were of marital status. MWL scoring in NASA-TLX revealed an average score of 70.91, which indicates a high MWL. Pearson’s correlation analysis unveiled that occupational fatigue and sleep quality were significantly correlated with sAA concentration. The final model showed that for each one-unit increase in occupational fatigue, the sAA concentration increased by 15.90 U/mL. Furthermore, for every unit increase in sleep quality, the sAA concentration decreased by 13.38 U/mL. sAA concentration can be used as a potential noninvasive biological marker related to sleep quality and occupational fatigue.